The Determinant Of Audit Fee For Micro, Small And Medium Enterprise : Evidence From Indonesia - Roza Mulyadi, I Made Narsa (International Journal of Advanced Science and Technology, 2020)
The importance of this research is conducted to determine the determinants of audit fees to micro, small, and medium enterprises in Indonesia. This research uses multiple regression analysis. The research sample of 444 public accounting firms in Indonesia at 104 MSMEs. The results showed that company size variables affected audit fees, profitability affected audit fees, company risk influenced audit fees, company complexity affected audit fees, industry influenced audit fees, Public Accountant Office status affected to audit fees, and audit report lag affects the audit fee.